Interactive Five Senses Garden: Enhancing Elementary Students' Long-Term Memory Retention through Three-Dimensional Diorama Learning - Siti Jamiyati; Erwinestri Hanidar Nur Afifi; Riska Latifatul Husna (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2026)
This study was motivated by the poor retention ability of third-grade students regarding the topic of the five senses, which tends to be abstract. The purpose of this study was to analyze the influence and effectiveness of using three-dimensional dioramas in improving students’ long-term memory retention. The method used was a quasi-experimental design with a non-equivalent control group. The research sample consisted of 31 students divided into an experimental class and a control class. Data were collected through retention ability tests measuring four specific indicators (recall, recognition, restating, and transfer of learning) administered before and after instruction. The results showed that the experimental class experienced a significant increase in retention ability, with the average score jumping from 40,13 to 79,20 (p < 0,05). Effectiveness measurements (N-Gain) indicated that the experimental class fell into the moderate category (0,65), while the control class experienced memory decay, falling into the low category (-0,06). In conclusion, the use of dioramas significantly and effectively facilitates dual coding to store information into long-term memory. These findings offer both theoretical and practical contributions to the development of interactive instructional media for elementary school teachers.